Integrasi SDGs dalam Perencanaan Strategis BUMKal: Studi Kasus di Binangun Raharja, Kalurahan Pagerharjo: Integrasi SDGs dalam Perencanaan Strategis BUMKal: Studi Kasus di Binangun Raharja, Kalurahan Pagerharjo - Suryanto, Rudy; Sofyani, Hafiez; Amalia, Rizka; Yani, Indah (JURNAL PENGABDIAN MANAJEMEN, 2026)
This community service program aims to improve the institutional capacity of the Village-Owned Enterprise (BUMN) Binangun Raharja, Pagerharjo Village, Kulonprogo Regency, by creating a sustainable strategic plan using the Sustainable Development Goals (SDGs). The main problems faced by the partners were the absence of sustainability-based strategic planning documents, weak community involvement, and minimal accountability reporting activities. This program was implemented in a participatory manner, namely through focus group discussions (FGDs), training, and strategic plan development workshops involving BUMKal administrators, academics, and the local community. The results of the community service program showed that participants gained a deeper understanding of the principles of sustainable development, institutional accountability, and the role of the community as part of business planning in the village. The results of this activity were a draft proposed BUMKal strategic plan in accordance with the SDGs, increased capacity of BUMKal managers in strategic planning, and identification of potential goat farming business units as a superior village product that can be introduced in the Red and White Cooperative Government program. The program provides a participatory, SDG-based approach to creating strategic plans for village-owned enterprises (BUMKal), which can improve the governance of village economic institutions in a more responsible and sustainable manner. Furthermore, it continues to support strategic plans and strengthens BUMKal performance reporting systems, and collaborates with local governments and other stakeholders to ensure the program’s sustainability and effectiveness in improving the well-being of village communities.